Simplifying
3x + 10 = 5x + 22
Reorder the terms:
10 + 3x = 5x + 22
Reorder the terms:
10 + 3x = 22 + 5x
Solving
10 + 3x = 22 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
10 + 3x + -5x = 22 + 5x + -5x
Combine like terms: 3x + -5x = -2x
10 + -2x = 22 + 5x + -5x
Combine like terms: 5x + -5x = 0
10 + -2x = 22 + 0
10 + -2x = 22
Add '-10' to each side of the equation.
10 + -10 + -2x = 22 + -10
Combine like terms: 10 + -10 = 0
0 + -2x = 22 + -10
-2x = 22 + -10
Combine like terms: 22 + -10 = 12
-2x = 12
Divide each side by '-2'.
x = -6
Simplifying
x = -6